Effect of Land Use Change on Gully Erosion Density in the Black Soil Region of Northeast China From 1965 to 2015: A Case Study of the Kedong County - Li, Maojuan; Li, Tianqi; Zhu, Lianqi; Meadows, Michael E.; Zhu, Wenbo; Zhang, Shuwen (Frontiers in Environmental Science, 2021)
Kedong County is typical of the black soil region of northeast China in being highly susceptible to accelerated soil erosion by gullying. Using data sourced from Corona satellite imagery for 1965, SPOT5 for 2005 and GF-1 for 2015, the spatial distribution of gullies in the research area was mapped. Land use data for 1965, 2005 and 2015 were obtained from the topographic map of 1954, and from Landsat images for 2005 and 2015. Over the last 50 years, the extent of gully erosion in the study area has increased markedly, most notably on cultivated land, while gully density rose from 2,756.16 m²/km² to 14,294.19 m²/km². Cultivating land on slopes, especially on slopes greater than ~4 degrees, may rapidly aggravate gully erosion. The greatest increases in gully density occurred in situations when cultivated land and other / degraded land were transformed, which gully erosion density increased by 49,526.69 m²/km². Other / degraded land is the most vulnerable land in the study area, with the highest gully erosion density. In these cases, gully density initially increases and, although the ‘Grain for Green’ project has been implemented, gully erosion density has not always declined in the recent past.